Prediction of problem gambling by demographics, gaming behavior and psychological correlates among gacha gamers: A cross-sectional online survey in Chinese young adults - Tang, Anson Chui Yan; Lee, Paul Hong; Lam, Simon Ching; Siu, Summer Cho Ngan; Ye, Carmen Jiawen; Lee, Regina Lai-Tong (Frontiers in Psychiatry, 2022)
Objective: The objective of this study is to explore the association of problem gambling with demographics, psychological distress, and gaming behaviour in young adult gacha gamers in Hong Kong. Methods: Cross-sectional data was collected in the first and fifth wave of COVID-19 pandemic in Hong Kong online. Participants who aged 18-25 years and had been playing gacha games over the past 12 months were recruited. Stepwise multiple regression was used to explore the association among risk of problem gambling, gaming behaviour, participation in gaming activities and psychological distress. A two-sided p-value <0.05 was considered as statistical significance. Results: Three hundred and thirty-seven completed questionnaires were received with no missing data. 34.7% (n=117) of the participants had non/low-risk of problem gambling. About 40% (n=136) of them had moderate-risk and the remaining 25%(n=84) were at high risk of problem gambling. A higher proportion of female participants (78.6%) was found in high-risk group as compared to 39.7% and 55.6% only in the non/low-risk and moderate-risk groups respectively. The regression model (R2 =0.513, F=71.895, p=0.000) showed that 51.3% of the variance of the total problem gambling score could be explained by stress, anxiety, monthly expenses on gacha purchases, number of motives for gacha purchase and number of gambling activities engaged. Conclusion: The present study provides empirical evidence to support the association between problem gambling and microtransaction especially for gacha which is the most popular type of in-game microtransaction in Asia. The established regression model suggests that gacha gamers with higher risk of problem gambling tend to have greater stress, higher anxiety level, spend more on gacha purchase, have more motives for gacha purchases and engage in more gambling activities. In contrast to the extant literature, higher proportion of female participants in high-risk group indicates that female gacha gamers are also at very high risk of becoming problem gamblers.